Ground-based detection of a cloud of methanol from Enceladus: when is a biomarker not a biomarker?. Issue 1 (18th December 2017) - Drabek-Maunder, E.; Greaves, J.; Fraser, H. J.; Clements, D. L.; Alconcel, L.-N.
ABSTRACT: Saturn's moon Enceladus has vents emerging from a sub-surface ocean, offering unique probes into the liquid environment. These vents drain into the larger neutral torus in orbit around Saturn. We present a methanol (CH3 OH) detection observed with IRAM 30-m from 2008 along the line-of-sight through Saturn's E-ring. Additionally, we also present supporting observations from the Herschel public archive of water (ortho-H2 O; 1669.9 GHz) from 2012 at a similar elongation and line-of-sight. The CH3 OH 5(1, 1)-4(1, 1) transition was detected at 5.9 σ confidence. The line has 0.43 km s −1 width and is offset by +8.1 km s −1 in the moon's reference frame. Radiative transfer models allow for gas cloud dimensions from 1750 km up to the telescope beam diameter 73 000 km. Taking into account the CH3 OH lifetime against solar photodissociation and the redshifted line velocity, there are two possible explanations for the CH3 OH emission: methanol is primarily a secondary product of chemical interactions within the neutral torus that: (1) spreads outward throughout the E-ring or (2) originates from a compact, confined gas cloud lagging Enceladus by several km s −1 . We find either scenario to be consistent with significant redshifted H2 O emission (4 σ ) measured from the Herschel public archive. The measured CH3 OH:H2 O abundance (>0.5%) significantly exceeds the observed abundance in the direct vicinity of the vents ( 0.01%), suggesting CH3 OH is likely chemically processed within the gas cloud with methane (CH4 ) as its parent species.